2009
DOI: 10.1007/s12602-009-9008-9
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media: A Review, with a Focus on Alternative Treatments

Abstract: Otitis media (OM) is the accumulation of fluids in the middle ear, with or without symptoms of inflammation. The infection is caused by dysfunction or obstruction of the eustachian tube and is most commonly diagnosed in children under the age of two. The microbiology of OM differs, with Streptococcus pneumoniae, non-typeable Haemophilus influenzae and Moraxella catarrhalis the most commonly isolated pathogens. The emergence of penicillin-resistant Strep. pneumoniae, β-lactamase-producing strains, Haem. influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…Bacteriocin production is considered a probiotic feature, and it has convincingly been shown that bacteriocin-producing probiotic lactic acid bacteria can inhibit growth of Listeria monocytogenes in mice (10). Thus, identification and characterization of bacteriocin-producing LAB of human origin are needed not only to develop probiotic bacteria with diverse antimicrobial potentials but also to develop bacteriocins into chemotherapeutic agents to control infections (12,47). To this end, we aimed at isolation of bacteriocin-producing LAB from healthy human infants.…”
mentioning
confidence: 99%
“…Bacteriocin production is considered a probiotic feature, and it has convincingly been shown that bacteriocin-producing probiotic lactic acid bacteria can inhibit growth of Listeria monocytogenes in mice (10). Thus, identification and characterization of bacteriocin-producing LAB of human origin are needed not only to develop probiotic bacteria with diverse antimicrobial potentials but also to develop bacteriocins into chemotherapeutic agents to control infections (12,47). To this end, we aimed at isolation of bacteriocin-producing LAB from healthy human infants.…”
mentioning
confidence: 99%
“…This study describes the condition OM, outlines existing treatment options, and offers another safe and herbal remedies that should be investigated. [1] • Murphy et al (2005) have investigated the vaccines for otitis media: ideas for overcoming roadblocks.…”
Section: Application Of Poloxamer 407 As Otic Drug Delivery Systemmentioning
confidence: 99%
“…O tic refers to hearing problems. [1] The human ear is one of the most remarkable aspects of the human body, not only for the beauty and uniqueness of its form but also for its extraordinary sensitivity to sound sensation. [2,3] The ear is traditionally split mainly into three sections, namely, the exterior, middle, and inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…The healthcare cost due to ear infections in the U.S. is estimated to be $3-5 billion annually [6][7][8]. There are three types of OM, acute otitis media (AOM), otitis media with effusion (OME), and chronic otitis media with effusion [9][10][11][12][13]. AOM occurs in the middle ear due to bacterial infection resulting in the buildup of fluid.…”
Section: Introductionmentioning
confidence: 99%